Alleviation of salinity stress on Vicia faba L. plants via seed priming with melatonin (2015)
Melatonin is an environmentally friendly-molecule with a potent free radical scavenger and antioxidant capacity. Two pot experiments were conducted during two successive winter seasons (2011/2012 and 2012/2013) at the wire-house of the National Research Centre, Dokki, Cairo, Egypt to study the potentiality of melatonin (100 mM and 500 mM) in alleviating the harmful effect of diluted sea water at a relatively low and high concentrations (3.85 dS/m and 7.69 dS/m, respectively) on the performance of faba bean plant. The results revealed that irrigation of faba bean plants with diluted sea water reduced growth parameters (plant height, leaves number/plant, fresh and dry weights /plant), relative water content (RWC), photosynthetic pigments (chlorophylls a, b and carotenoids), indole acetic acid, total carbohydrate, K+,Ca+2, as well as the ratios of K+/Na+ and Ca+2/Na+ .Thiswasaccompanied by significant increases in phenolic content, compatible solutes (total soluble carbohydrate, free amino acids, proline), Na+ and Cl- , relative to the control plants (untreated plants). On the other hand, melatonin treatments improved growth parameters, RWC, photosynthetic pigments, total carbohydrate, total phenolic content, indole acetic acid, K+,Ca+2 as well as K+/Na+ and Ca+2/Na+ ratios, either in the plants irrigated with tap water or with diluted sea water, as compared with corresponding controls. Meanwhile, melatonin treatments reduced the levels of compatible solutes, as well as Na+ and Cl-  contents, relative to those of corresponding controls. Salinity stress and/ or melatonin treatments induced the production of new protein bands that did not occur in the control plants. Melatonin at 500 mM had a more pronounced effect in alleviating the adverse effects of the two salinity levels under study on the performance of faba bean plants than 100 mM melatonin.